Azoxystrobin resistance of Botrytis cinerea Pers.:Fr. isolates - Takács, Ferenc; Asadollahi, Mojtaba; Karaffa, Erzsébet (Acta Agraria Debreceniensis, 2011)
Fungicide resistance is one of the most important problems endangering the effectivity of practical plant protection today. The frequent and subsequent usage of specific fungicides results the emergence of resistant fungal populations. This threatens is especially high in case of Botrytis cinerea Pers.:Fr. being an endemic pathogen with frequent infection. Nowadays the main method of protection as against Botrytis cinerea is the application of chemical fungicides chemicals. Therefore, a better knowledge of local populations is necessary for the planning of the protection procedures.Based on the results of our examinations we may establish that the growth of the examined samples showed a significant difference under in vitro circumstances, which shows a great deal of variability of the Botrytis cinerea populations in Hungary. Twenty-five Botrytis cinerea samples from different hosts were analyzed in this study. High resistance was found towards azoxistrobin in seven cases, and low resistance in eight cases.It was also proved, that the B. cinerea is able to bypass the inhibition site of the azoxistrobin via the alternative oxidase. The presence of this altermative mitocondrial electrotransport route considerably reduces the effectivity of the chemical.